DNA methylation and gene expression regulation associated with vascularization in Sorghum bicolor. Issue 3 (10th February 2017) - Turco, Gina M.; Kajala, Kaisa; Kunde‐Ramamoorthy, Govindarajan; Ngan, Chew‐Yee; Olson, Andrew; Deshphande, Shweta; Tolkunov, Denis; Waring, Barbara; Stelpflug, Scott; Klein, Patricia; Schmutz, Jeremy; Kaeppler, Shawn; et al.
Summary: Plant secondary cell walls constitute the majority of plant biomass. They are predominantly found in xylem cells, which are derived from vascular initials during vascularization. Little is known about these processes in grass species despite their emerging importance as biomass feedstocks. The targeted biofuel crop Sorghum bicolor has a sequenced and well‐annotated genome, making it an ideal monocot model for addressing vascularization and biomass deposition. Here we generated tissue‐specific transcriptome and DNA methylome data from sorghum shoots, roots and developing root vascular and nonvascular tissues. Many genes associated with vascular development in other species show enriched expression in developing vasculature. However, several transcription factor families varied in vascular expression in sorghum compared with Arabidopsis and maize. Furthermore, differential expression of genes associated with DNA methylation were identified between vascular and nonvascular tissues, implying that changes in DNA methylation are a feature of sorghum root vascularization, which we confirmed using tissue‐specific DNA methylome data. Roots treated with a DNA methylation inhibitor also showed a significant decrease in root length. Tissues and organs can be discriminated based on their genomic methylation patterns and methylation context. Consequently, tissue‐specific changes in DNA methylation are part of the normal developmental process.